Debt collectors [videorecording (DVD)] - Small, Stu; Adkins, Scott, 1976-; Mandylor, Louis; Kulich, Vladimir, 1956-; Johnson, Jesse V., 1971-; Johnson, Jesse V., 1971- (Samuel Goldwyn Films, 2020)
Debt collectors French and Sue get to work doing what they do best, cracking skulls and breaking bones, as they chase down the various lowlifes who owe money to their boss, Tommy. They're summoned to Las Vegas to collect from a dirty casino owner. Meanwhile, a notorious drug kingpin is on the warpath to kill French and Sue to avenge his brother's death. Facing danger from all angles, the pair will have no other choice but to fight their way out of a dangerous situation.